2017
DOI: 10.3892/mmr.2017.7312
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-302a inhibits cell proliferation and invasion, and induces cell apoptosis in hepatocellular carcinoma by directly targeting VEGFA

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer and the third most common cause of cancer‑related mortality worldwide. An increasing number of studies have demonstrated that microRNAs may be used as diagnostic, therapeutic and prognostic targets for human cancers, including HCC. The present study aimed to evaluate microRNA (miR)‑302a expression and function in HCC, and its underlying mechanisms. The results revealed that miR‑302a was expressed at low levels in HCC tissues and cell lines. Reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…qRT-PCR, Western blot and luciferase reporter assay results confirmed that VEGFA was a direct target of miR-302 cluster. These findings were consistent with a previous study in which Qin et al reported that miR-302a inhibited hepatocellular carcinoma cell proliferation and invasion through targeting VEGFA 32. We further revealed that there was a negative correlation between miR-302 cluster and VEGFA mRNA level in CML patients.…”
Section: Discussionsupporting
confidence: 93%
“…qRT-PCR, Western blot and luciferase reporter assay results confirmed that VEGFA was a direct target of miR-302 cluster. These findings were consistent with a previous study in which Qin et al reported that miR-302a inhibited hepatocellular carcinoma cell proliferation and invasion through targeting VEGFA 32. We further revealed that there was a negative correlation between miR-302 cluster and VEGFA mRNA level in CML patients.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, knockdown of HMGA2 expression, increased the expression of miR-302a-5p/367-3p. Besides HMGA2, miR-302a or miR-367-3p may target multiple genes and pathways to inhibit tumour growth and metastasis [ 43 , 44 ]. This indicates that the combination of agomirs and target genes may be more effective in the inhibition of tumour growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that tumor necrosis was related to advanced stage and worse survival in rectal cancer patients ( 48 ), and WRAP53 level was significantly increased in primary tumor compared to normal mucosa, which was associated with poor prognosis ( 39 ). In fact, the reduced expression of miR-302a has been frequently reported in several types of malignancies, such as breast cancer ( 21 ), HCC ( 22 ), prostate cancer ( 23 ), cervical cancer ( 24 ), and skin cancer ( 25 , 26 ). However, miR-302a was found to be overexpressed in CRC ( 20 , 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of miR-302a in breast cancer cells plays an important role in regulation of invasion and metastasis of breast cancer ( 21 ). The low expression of miR-302a inhibits cell proliferation and invasion and induces cell apoptosis in HCC by directly targeting vascular endothelial growth factor-A ( 22 ). The overexpression of miR-302a in prostate cancer cells can induce cell cycle arrest and inhibit cell proliferation in vitro and tumor formation in vivo ( 23 ).…”
Section: Introductionmentioning
confidence: 99%